MUSEUM TARI DI MAKASSAR DENGAN PENDEKATAN EKSPOSE STRUKTUR PADA FASAD BANGUNAN DAN PENERAPAN TEORI FRAKTAL - Arfan, Taufik; Jaharuddin, Wahyuni (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2015)
The importance of dance in Makassar museum is to introduce a culture held in South Sulawesi, which can be known by all foreign countries, as well as parawisatawan and everyone to visit. The research objective non architecturally it is featuring elements of culture, history and introduce Traditional Dance in South Sulawesi, while the purpose of the architectural is to determine the location that corresponds to the existence of the museum of dance, designing spaces required in accordance with the standards Museum as well as the need for space for art museum dance, design a museum of dance that is associated with exposure to the facade structure and merger with fractal theory, designing the use of facades of buildings, structures, utilities, appearance of the building, as well as the transformation of the museum forms of dance and design the masses on the dance museum. This report is the result of designing the museum building in Makassar dance with exposure approach to the structure of the building facade and application of fractal theory adapted to the standards and needs of the space.